The genetic diversity analysis in the donkey myostatin gene - Dong-hua LIU; Hao-yuan HAN; Xin ZHANG; Ting SUN; Xian-yong LAN; Hong CHEN; Chu-zhao LEI; Rui-hua DANG (Journal of Integrative Agriculture, 2017)
Myostatin (MSTN) gene negatively controls skeletal muscle development and growth, variations of which play an important role in the regulation of skeletal muscle growth in mammals. However, study on genetic polymorphism ofMSTN gene in donkey is limited. In this study, we screened the single nucleotide polymorphsims (SNPs) ofMSTN gene in 13 Chinese donkey breeds. Four novel SNPs (g.229T>C, g.872A>G, g.2014G>A, and g.2395C>G) were detected and genotyped by sequencing and polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) methods. Six haplotypes (H1-H6) were analyzed, which indicated abundant haplotype diversities in Chinese donkeys. The haplotype H1 was the most dominant and ancient in all breeds. Xinjiang donkey displayed the highest haplotype diversity. The Neighbour-Joining (NJ) tree ofMSTN gene among different species was constructed. The clustering result of nine species was consistent with the fact of species differentiation. Our results will provide a reliable theoretical basis for the preservation, exploration and utilization of Chinese donkey genetic resources.